Theoretical Prediction of Mixing Efficiency in Stratified Shear Exchange Flows - Tjipto Prastowo (Jurnal Matematika & Sains, 2009)
Mixing efficiency in stratified shear exchange flows between two reservoirs of water of differing densities is analytically investigated in detail in the light of a two-layer flow. The theoretical prediction of mixing efficiency is presented here in terms of a scaling analysis developed for such flows. The prediction is compared with that derived from measurements of normalised density profiles. The predicted mixing efficiency is found to be 0.125, independent of flow conditions and external parameters used. This value is approximately the same as 0.12, obtained from the averaged density profiles, and is close to a half of 0.2, the widely proposed value for the average efficiency in the oceans that is frequently assumed in general ocean circulation modeling.